A fermentative approach to ameliorating solid waste challenges within food and hospitality industry - Jamal, Parveen; Olorunnisola, K.S; Abdul Karim, Mohamed Ismail; Alam, Md. Zahangir; Suleyman, Aremu Muyibi (2014)
Solid wastes emanating from food and hospitality domains constitute environmental challenges and their holistic management remained inevitable. Solid state bioconversion process involving mixed culture of microbes was conducted for 7 days. Bio-product synthesis by the microorganisms and bio-degradation extent of fruit peels’ components were analyzed for chemical and structural changes. Chemical analysis showed improved protein enrichment when microbes were mixed together at different ratios (141.18 mg/g) compared with 4 cm apart (115.62 mg/g). Through substrate reformulation, fermentable sugar composition rose to 500.99 mg/g and protein enrichment increased to 160.68 mg/g, cellulase activity was 1.33±0.04 units/ml and α-amylase activity of 112.46±0.28 units/ml was synthesized. Analysis of reformulated substrates indicated presence of more metabolizable sugar while FT-IR analysis revealed immense modifications and consumption of complex sugars (cellulose, hemicellulose and lignin) by selected filamentous fungi